2001
DOI: 10.1016/s1074-7613(01)00085-1
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 and NFATc2 Together Control Both T and B Cell Activation and Differentiation

Abstract: NFAT transcription factors play critical roles in gene transcription during immune responses. To investigate further the two most prominent NFAT family members, NFATc1 and NFATc2, we generated mice bearing lymphoid systems devoid of both. Doubly deficient T cells displayed cell surface markers of activation yet were significantly deficient in the development of multiple effector functions, including Th cytokine production, surface effector molecule expression, and cytolytic activity. Nevertheless, doubly defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
267
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(278 citation statements)
references
References 37 publications
8
267
0
3
Order By: Relevance
“…Another transcription factor that is involved in IL-4 gene expression and is regulated by TCR signaling is NFAT. Both NFATc2 and NFATc1 bind to the IL-4 locus and enhance gene expression (43). We previously have shown that inhibition of NFAT in CD4 ϩ T cells interferes with Th2 immune response and the development of allergic airway inflammation (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another transcription factor that is involved in IL-4 gene expression and is regulated by TCR signaling is NFAT. Both NFATc2 and NFATc1 bind to the IL-4 locus and enhance gene expression (43). We previously have shown that inhibition of NFAT in CD4 ϩ T cells interferes with Th2 immune response and the development of allergic airway inflammation (44).…”
Section: Discussionmentioning
confidence: 99%
“…NFAT is a transcription factor whose activation is heavily dependent on increased intracellular calcium due to its dephosphorylation and nuclear trafficking by the calcium-dependent phosphatase, calcineurin (39). NFAT is involved in the regulation of IL-4 and both NFATc1 and NFATc2 have been shown to bind to the IL-4 locus and promote gene expression (43). We have shown that activation of NFAT in T cells is required for Th2 immune responses and allergic airway inflammation (44).…”
Section: Cd4 ϩ T Cells Isolated From Naive ⌬F508 and Cftr Mice Have Imentioning
confidence: 98%
“…It has been well characterized that redundancy within the NFAT family exists. In general, knocking out one NFAT protein results only in a mild phenotype, whereas knocking out two or more members leads to striking defects (45)(46)(47)(48)(49)(50)(51)(52)(53). The phenotypes of these mice seem to indicate that although NFAT1 and NFAT2 proteins regulate the expression of activation-induced genes, it is NFAT1 and NFAT4 that might be specifically involved in controlling cellular programs that lead to the negative regulation of T cell responses.…”
Section: Retroviral Infection Of Primary T Cellsmentioning
confidence: 99%
“…It has been shown that several NFAT family members, such as NFAT1 and NFAT2, are expressed in B lymphocytes and are required for B cell development and function upon activation. [32][33][34] Together with NFAT4, NFAT1 has been described to be involved in the expansion of mature follicular B cells, 35 and in B cell tolerance. 36 However, the role of NFAT1 transcription factor in cell cycle control of B lymphocytes remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%